Water characteristic curves of recycled materials - Rahardjo, Harianto (2011)
Water characteristic curves (WCCs) of recycled materials are not well researched. In this study, the WCCs of three specimens from recycled concrete aggregate, three specimens from reclaimed asphalt pavement, and one specimen from spent copper slag are studied. The objective of this study is to obtain WCCs of the recycled materials by using the Tempe cell pressure extractor for standard soil-water characteristic curve determination. Properties of drying WCC of the recycled materials were determined by using a best fit WCC equation. The results showed air-entry value of the recycled materials with high gravel content that occurred at low matric suction below 1.0 kPa and a steep WCC. The results from the WCC and saturated coefficient of permeability tests were incorporated into a statistical model to indirectly predict the permeability function of the recycled materials. The permeability functions of the recycled materials are also presented.